(4x^2 + 6x + 3) + (2x^2 - 5x - 3)

(4x^2 + 6x + 3) + (2x^2 - 5x - 3) = 6x^2 + x

Question

Asked 12/18/2010 11:29:55 PM

Updated 4/18/2015 2:04:14 PM

1 Answer/Comment

Edited by Andrew. [4/18/2015 2:04:12 PM]

s

Rating

8

(4x^2 + 6x + 3) + (2x^2 - 5x - 3)

= 6x^2 + x

= 6x^2 + x

Added 4/18/2015 2:04:14 PM

This answer has been confirmed as correct and helpful.

Working with polynomial: (8x – 5) + (7x + 4) **Weegy:**
(8x – 5) + (7x + 4)
= 8x + 7x - 5 + 4
= 15x - 1
(More)

Question

Expert Answered

Updated 6/23/2020 6:24:21 AM

0 Answers/Comments

Working with polynomial: (5x – 3.6) – (4x + 1.2)

Question

Expert Answered

Updated 7/3/2014 1:57:21 PM

1 Answer/Comment

Working with polynomial: (3x^2 + 3x) + (4x + 4). Please show the steps on how you got your answer. Thanks!

Question

Updated 8/10/2014 5:55:48 PM

1 Answer/Comment

(3x^2 + 3x) + (4x + 4)

= 3x^2 + 3x + 4x + 4;

= 3x^2 + 7x + 4

= 3x^2 + 3x + 4x + 4;

= 3x^2 + 7x + 4

Added 8/10/2014 5:55:48 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/10/2014 5:57:18 PM]

34,040,311

questions answered

There are no comments.